Citronella is promising for Sikkim - Kalita, H; Babu, Subash; Yadav, G S; Helim, R; Das, B (Indian Horticulture, 2015)
The genetic diversity of both forest vegetation and agricultural crops, is enormous. Various aspects of production and management of aromatic plants had not received proper attention in the state. Aromatic plants are generally perceived to be hardy and suitable for cultivation in wastelands, marginal lands and problematic lands. Citronella is an important crop to address in this respect. Sikkim, being an organic state, organic production of aromatic plants has to be market-driven for it to be successful.